Web-Based home marketing information system at CV Abah Ipin using Php and Mysql - Rahman, Moh. Didi; Surono, Surono (Jurnal Mandiri IT, 2024)
CV Abah Ipin is a company engaged in the construction and marketing of houses in tegal district. In marketing activities, CV Abah Ipin still uses conventional methods, namely printing and distributing brochures. Conventional marketing techniques are inefficient because they are unable to reach a large enough number of potential customers. In addition, conventional marketing techniques are inefficient because they require a lot of money to produce promotional materials such as brochures. In order to build a web-based home marketing information system for CV Abah Ipin, the author examines these problems as a solution to the problems of traditional marketing that are deemed inefficient and unsuccessful. The technique employed in this design is Waterfall with UML tools, also using MYSQL functions as a database and the PHP programming language helps develop websites. The design of this house marketing information system will produce a web that is expected to be a way to increase the effectiveness and efficiency of CV Abah Ipin's property marketing.